Madrasah Principal’s Strategies in Managing Conflict in Islamic Educational Institutions: A Case Study of MAS Al Washliyah, Pakam Village - Farihin Abdillah Fattah; Mesiono Mesiono; Makmur Sukri (MASI Mandiri Edukasi, 2026)
This study aims to analyze the dynamics of internal conflicts and the conflict-management strategies implemented by the Principal of MAS Al Washliyah Desa Pakam, Medang Deras District, Batu Bara Regency. Internal conflicts were found to occur repeatedly within the madrasah and involved various organizational components, including subject teachers, administrative staff, homeroom teachers, and guidance and counseling (BK) teachers. Using a qualitative approach, data were collected through observations, interviews, and documentation. The findings reveal that conflicts stem from weak interdepartmental communication, imbalanced workloads, differing perceptions of roles and responsibilities, and the absence of systematic internal coordination. The principal employs dialogic, collaborative, and democratic approaches to conflict resolution through deliberative forums, direct supervision, and rapid communication via digital media. These strategies are reinforced by Islamic values such as syura (consultation), ethical communication, and mutual respect, which enhance the effectiveness of conflict management. The study concludes that inclusive, participatory, and communicative leadership plays a critical role in maintaining organizational stability, strengthening professional relationships, and preventing persistent conflicts. Therefore, systematic improvements in the madrasah’s governance are necessary to support the creation of a harmonious and productive educational environment.